Viable Shattercane Seed - Hickok, Kyle; Dille, J. Anita (My University, 2018)
a. Shattercane is a common weed that many farmers all over Kansas have to deal with. This project should help farmers get a better idea when those shattercane plants become able to reproduce.!b. When does shattercane heads become a potential problem to produce viable seeds?!c.The control group of fully mature shattercane seeds where the only seeds that sprouted in the 5 day test period. I found that more time may be necessary for the less mature seeds to sprout. !d. The results from this testing can be important to farmers to know when they need to take action to decrease risks of shattercane problems in the future!
Keywords: Fall 2018